Swift data structure and algorithms : master the most common algorithms and data structures, and learn how to implement them efficiently using the most up-to-date features of Swift 3 /: master the most common algorithms and data structures, and learn how to implement them efficiently using the most up-to-date features of Swift 3. (2016) - Azar, Erik; Eguiluz Alebicto, Mario
No abstract available